Tối ưu hoá sử dụng mạng nơ ron và ứng dụng trong điều khiển tự động - Hỷ, Chu Văn (Journal of Computer Science and Cybernetics, 2016)
This paper reviews the theoretical basis for using neural networks to optimization, and presents two applications in automatic control: on-line identification and pole assignment synthesis of linear systems.